1976-2006. From research journalism to critic cyber journalism in Mexico. From the weekly magazine Proceso to the Reporte Índigo - Islas, Octavio (2008)
For not few generations Proceso has been the only mean to get information better than the one in Mexico’s normal media offers, which almost never has the kind of hard critical journalism. In recents years, the shift to knowledge economy has imposed great changes in the overall media. Today, the use of the internet is now mandatory. Reporte Indigo is placed among a reduced number of media, born inside the web, that understand thesis “the medium is the message”.